(untitled) (Jurnal Tata Kelola Pendidikan, 2021)
This research aims to know the influence of job satisfaction on organizational commitment of non-civil servant employees in The West Java Provincial Departement Of Education. The method used in this research was a descriptive method with a quantitative approach. The data collection technique used was questionnaire that distributed to 83 research respondents. The WMS (Weight Mean Score) calculation result shows that of both variable X and variable Y is at good category. The correlation coefficient between Job Satisfaction and Organizational Commitment obtained a score of 0.644, which was included in the "strong" category. Meanwhile, the result of significance test shows the value of tcalculation for 7,572 and ttable for 1,989 (tcalculation > ttable), it means that there is a significant relationship between variable X and variable Y. The influence of the Job Satisfaction on Organizational Commitment obtained from from the results of the determination test is 41.4% and the rest is influenced by other factors. The result of coefficient of determinition test shows 40,393 + 0,644X, means that each addition on the X variable will increase the Y variable value of 0.644. Based on the result, it can be concluded that there is a positive and significant influence between the Job Satisfaction On Organizational Commitment Of Non-Civil Servant Employees In The West Java Provincial Departement Of Education.